Evaluating Attributes, Traits, and Competencies of a School Leader: A Descriptive-Correlational Study - Leomarich Casinillo; Michael Suarez (Indonesian Journal of Social Research (IJSR), 2022)
Evaluation of the different characteristics of a school leader in the Philippines is a bit limited in educational literature. Hence, this study focus on assessing the personal attributes, traits, and competencies of school leaders in the Hindang District, Leyte Division, Philippines to elucidate its nature and promote new policy in improving the educational system. This study employed a cross-sectional data gathering from a complete enumeration of teachers in the district. Mean, standard deviation, and coefficient of variation were computed in describing the survey data, and Spearman rho correlation was utilized in determining the association between variables. Results showed that school leaders are rated as "very satisfactory" concerning their "personal attributes", "traits", "result-focus", "self-orientation", "innovation", "leading people", "people performance and management", and "people development" characteristics. School leaders are also rated as "outstanding" in terms of their competencies such as "self-management", "professionalism and ethics", and "teamwork." The correlation matrix revealed that all the characteristics of a school leader are positively correlated (strong) to each other at a 1% level of significance. Hence, it is concluded that each character is a very important asset for a school leader in developing the school. This implies that to attain continuous progress in a school, the qualification in hiring a school leader must focus on personal attributes, traits, and competencies, not on the curriculum knowledge. Furthermore, a school leader must undergo seminars and training that deal with lead management and innovative ideas to become globally competitive leaders.